International Symposium on Fisheries Economics (Paris, 1971)
Contents: fisheries management and the law of the sea; Practical problems of policy formulation; Stock assessment and forecasting; regulation production; tuna fishing,...
Keywords: Fishery management,Quản lý thủy sản